Validity of Sanctions for Imposing Vaccination Fines Covid-19 - Nurmi Aliyatul Syakira (LEGAL BRIEF, 2022)
This study aims to determine how the legal position of Presidential Decree No. 14 of 2021 as the basis for setting up the sanctions for the Covid-19 vaccination fine and also to find out how effective the law is in setting the sanctions for the Covid-19 vaccination fine. This research is normative legal research (doctrinal law), namely legal research that examines written law in laws and regulations (law in books) or laws that are conceptualized as rules or norms that guide behavior. With data collection techniques through library research, namely reviewing relevant laws and regulations that support arguments in research and conducting observations through direct interviews with the Head of the Management and Development of the Covid-19 Vaccination Implementation and Functional Coordinator of Legal Counsel for the Mayor of Makassar. In addition to using a conceptual approach, the author also conducts library research through data and books related to the research topic. Furthermore, the data obtained were analyzed qualitatively which was then presented descriptively. The results of this study are: 1) In an emergency, the Government (President) is given the authority to make a statutory regulation to overcome the problems being faced. However, the government must still pay attention to the limits of this authority and continue to pay attention to the rules for the formation of laws and regulations. When this Presidential Regulation is considered as part of binding statutory regulations in general, not as beleidregels , this regulation should have a basis in the form of a law that regulates or PP in advance as the contents of the contents of the Presidential Regulation are material ordered by law or material to implement PP. The Birth of the Supreme Court Number 31 P/HUM/2022 which states that the provisions of Article 2 of Presidential Regulation No. 99 of 2020 does not have binding force because it is contrary to the Halal Product Guarantee Act, then immediately the provisions governing vaccine obligations also do not have binding force. 2. Provisions for regulated fines in Presidential Decree No. 14 of 2021 in fact is not implemented or enforced so that the effectiveness of this regulation also participates questionable because effective law in general can make what is designed can be realized.